The Welfare Effects of Social Assistance Programs for Women in India. Issue 6 (3rd June 2022) - Unnikrishnan, Vidhya
Abstract : Literature has established that the alarming female poverty rate is a crucial factor contributing to missing older women in India. Given this, the following research examines the role of an unconditional cash transfer programme (Indira Gandhi National Old Age Pension Scheme) implemented in India on the household budget share incurred on cereals, pulses, vegetables; fruits and nuts, meat; eggs and fish, milk and milk products when the program recipient is an elderly woman. The paper uses the longitudinal household-level data (2004–05 and 2011–12) released by the India Human Development Survey and utilises a quasi-experimental framework of propensity score matching combined with fixed effects to estimate the effects of the pension on the disaggregated food budget share incurred by the pension recipient households. The findings in this paper suggest that women's access to pension has a positive effect on budget share allocated on vegetables, fruits and nuts and meat, fish and eggs. The positive effects persist for continuous program recipients. Further, to address any concerns on endogeneity, an instrumental variable strategy has been used. This paper provides evidence that female pension recipient households in India do move towards nutrient-rich food items.